Review of Lim, Lily, & Defeng D. (eds.). 2020. Key Issues in Translation Studies in China: Reflections and New Insights. Springer: Singapore. 203 pp. eBook ISBN: 978-981-15-5865-8 - Xuan Liu (Russian Journal of Linguistics)
-